Unveiling the protective role of anthocyanin in rice: insights into drought-induced oxidative stress and metabolic regulation - Jan, Rahmatullah; Asif, Saleem; Asaf, Sajjad; Lubna,; Khan, Zakirullah; Kim, Kyung-Min (Frontiers in Plant Science, 2024)
This study investigates the impact of anthocyanin treatment on rice plants under drought stress, focusing on phenotypic, molecular, and biochemical responses. Anthocyanin-treated plants exhibited significant enhancements in various traits, including growth parameters and reproductive characteristics, under normal conditions. When subjected to drought stress, these plants displayed resilience, maintaining or improving essential morphological and physiological features compared to non-treated counterparts. Notably, anthocyanin application mitigated drought-induced oxidative stress, as evidenced by reduced levels of reactive oxygen species (ROS) and lipid membrane peroxidation. The study also elucidates the regulatory role of anthocyanins in the expression of flavonoid biosynthetic genes, leading to increased levels of key secondary metabolites.Furthermore, anthocyanin treatment influenced the levels of stress-related signaling molecules, including melatonin, proline, abscisic acid (ABA), and salicylic acid (SA), contributing to enhanced stress tolerance. The enzymatic activity of antioxidants and the expression of droughtresponsive genes were modulated by anthocyanins, emphasizing their role in antioxidant defense and stress response. Additionally, anthocyanin treatment positively influenced macronutrient concentrations, particularly calcium ion (Ca + ), potassium ion (K + ), and sodium ion (Na + ), essential for cell wall and membrane stability. The findings collectively highlight the multifaceted protective effects of anthocyanins, positioning them as potential key players in conferring resilience to drought stress in rice plants. The study provides valuable insights into the molecular and physiological mechanisms underlying anthocyanin-mediated enhancement of drought stress tolerance, suggesting promising applications in agricultural practices for sustainable crop production.